BIOPROSPECÇÃO DAS FOLHAS, CASCA E LÁTEX DA ESPÉCIE VEGETAL Himatanthus drasticus (JANAÚBA) - Coutinho, Gizelli Santos Lourenço (2013)
Himatanthus drasticus (janaúba) is a tree with dense foliage at the ends of branches, oblique and ovals leaves, subcoriaceous, shiny, glabrous, dark green, with apex rounded to obtuse, short petioles and rough bark that exudes a white latex widely used in popular medicine in treatment of tumors, worms, gastritis, arthritis, infertility and also cancer. Therefore, this study aims to do an ethnopharmacological survey, determine the phytochemical and metal compositions, and to evaluate the antioxidant and microbiological activity of the hydroalcoholic extract from the leaves, bark and latex of the plant species Himatanthus drasticus. Qualitative tests were conducted for detection of secondary metabolites, and mineral detection was performed by atomic absorption (ICP-OES technique). In relation to the antioxidant activity was used in vitro method with DPPH and for antimicrobial activity have been used standard strains (ATCC) of gram-positive bacteria (Staphylococcus aureus, Streptococcus agalacicus), gram-negative (Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis) and yeasts of Candida gender (C. albicans, C. parapsilosis, C. tropicallis, C.glabrata) through tests in diffusion in the solid and in agar diffusion, determining the Minimum Inhibitory Concentration (MIC). Regarding the popular use in Maranhão is indicated for: inflammation, inflammation on uterus, gastritis, ulcers, blood cleanser, prostate, cancer, as restorative and against infertility. Were found in the leaves of Himatanthus drasticus flavonoides, condensed tannins, alkaloids, steroid free, triterpenes, saponins, resins, coumarins. In barks, were found strongly positive results for anthocyanins, flavonoids and anthocyanidins. In the bark and latex were detected the presence of steroids and triterpenoids. Still in the bark was found a great percentage of calcium, potassium and magnesium, in the latex was observed higher percentage of calcium, magnesium and in the leaves the predominance of minerals like calcium, potassium, phosphorus and magnesium. The hydroalcoholic extract of the bark and leaves of H. drasticus showed significant antioxidant activity with EC50% 27.8848 9g / mL and CE50 of 31.62 9g / mL, respectively. In vitro testing was observed inhibition of growth of the tested strains with hydroalcoholic extract from the bark and leaves of H. drasticus, but the latex was inactive. Only the latex has caused cell death in the title 1:16 in carcinoma larynx cell (HEP-2) and 1:8 in uterine carcinoma cell (Hela). Therefore, further studies should be conducted to better scientific understanding of the species H. drasticus